Functional Electrical Stimulation dengan Pulsa Biphasic Untuk Membantu Fungsi Ekstremitas Atas Pasien Pasca Stroke - Deny Arifianto (Jurnal Biosains Pascasarjana, 2021)
Abstract Stroke or nerve function disorders caused by disruption of blood flow to the brain that arises suddenly or quickly with symptoms or signs that correspond to the affected area. One of the post-stroke rehabilitation using electrical stimulation, also known as an electro stimulator. This study aims to design Functional electrical stimulation (FES), which aims to stimulate the peripheral nervous system with biphasic pulses. Stimulation for patients with MMT 1 was optimal at a frequency of 22-30 Hz. In post-stroke patients with MMT inclusion characteristics 0-3, a minimum voltage, frequency and pulse width value of 200 Vp, 22 Hz, and 20 s is required with a power of 0.00146 Watt. Studies have shown that this electro stimulator device had good accuracy and has high peak voltage values and low effective current. It can be considered because it provides comfort and safety for medical therapy equipment.